Coping with the coronavirus (COVID-19) pandemic - Aşkın, Rüstem; Tan Dinsel, Ezgi; Baş, Alper (The European Research Journal, 2020)
The global virus outbreak called COVID-19 has been one of the important breaking points in world history. COVID-19 is not only a physical disease affecting the whole world, but also an important issue in terms of community mental health, the effects of which will be understood in the long term. It is essential to explain the long-term and ongoing mental health effects of COVID-19 to take preventive steps. The aim of the present article was to review the impact of similar outbreaks in the past and to understand the potential impact on mental health through data from ongoing studies. Additionally, we summarized possible risk factors that may arise in infected people, healthcare professionals and the general population during COVID-19 outbreak.